TINGKAT KEPUASAN PASIEN DAN KELUARGA TERHADAP PELAYANAN INSTALASI GAWAT DARURAT RUMAH SAKIT ADVENT BANDUNG - Jenny Tampubolon; Untung Sudharmono (Jurnal Skolastik Keperawatan, 2020)
Emergency Room (ER) services are the main entrance to the hospital for most patients. Service quality is determined by customer satisfaction, that is, if the service is relevant to the consumers’ expectations. This study was to determine between the level of satisfaction of the patients and their families with the ER services at Bandung Adventist Hospital. The level of satisfaction is measured by the five main dimensions of nursing service quality according to the order of their relative importance, including (1) Reliability; (2) Responsiveness; (3) Assurance; (4) Empathy; and (5) Tangible. The method used in this research is descriptive method through a quantitative approach. A sample of this study amounted to 269 respondents who were taken by accidential sampling technique. The results of this study indicate that the level of patient and patient satisfaction with Advent Bandung Hospital services shows that 59% (174 people) are very satisfied, 33% (99 people) are satisfied, 6.4% (19 people) feel sufficient 1% (3 people) felt very dissatisfied, 0.6% (1 person) felt less satisfied. Thus, the average value of the level of patient and family satisfaction with services in the emergency department of the Advent Bandung hospital was 92% (273 people), and the level of patient and family dissatisfaction with the emergency room services of the Advent Bandung Hospital had an average of 8%. Kays Words: Emergency Room, Satisfaction, Service.